Teaching strategies for reading comprehension development for 10th graders at Unidad Educativa Mariscal Sucre in the scholastic year 2022 – 2023. - Chaguay Acosta, Noan Eugenio (2023)
The following study focuses on determining the strategies the EFL teacher uses in the actual class for the development of reading comprehension skills among 10th grade students at Unidad Educativa Mariscal Sucre. An EFL proficiency test was carried out to measure the reading comprehension performance of the group. In addition, the teaching methodology applied by the instructor was evaluated through two checklists, and an interview, that was conducted to know the teacher’s perception of reading instruction. The research findings show that the group has problems with reading comprehension regarding interpreting texts and understanding the main idea and specific information from texts. It was also found that the teacher is concerned with activating students’ background knowledge, but does not promote the interpretation of texts in the classroom and the instructor´s strategies are limited. Other issues detected were the lack of contextualization of vocabulary and poor feedback. Based on the findings, a proposal was created for providing strategies that enhance reading comprehension instruction.